Peculiarities of antibiotic therapy after pancreaticoduodenectomy - Olga Yu. Gasieva; Igor E. Khatkov; Arkadiy L. Vertkin (ZAO "Consilium Medicum", 2023)
Aim. To reveal and evaluate predictors of infectious complications in the postoperative period after pancreatoduodenectomy. Materials and methods. An analysis was made of 790 articles that dealt with the subject of complications after pancreatoduodenectomy. Results. Seventy five articles met the inclusion criteria. Studies with small samples (less than 20 patients) were not considered. Based on the multifactorial nature of the problem of preventing infectious complications in the postoperative period, the results of the review are divided into several sections. PBD is highly effective in obstructive jaundice syndrome at the preoperative stage, but is associated with the risk of bile infection and complications in the postoperative period. These circumstances should be taken into account when determining the indications for PBD, choosing the method of decompression, in cases where stenting is used, attention should also be paid to the choice of material. Bacteriobilia is an independent predictor of surgical site infections (SSI) after PDR. Conclusion. Changing the approach to antibiotic prophylaxis based on the antibiotic sensitivity of the microflora can lead to a decrease in the incidence of SSI, a reduction in the duration of hospitalization, the number of complications associated with long-term antibiotic therapy, a decrease in the rate of spread of antibiotic resistance and a decrease in the financial costs of the institution for a completed case of medical care.